Operation Red Sea [videorecording (DVD)] - Lin, Chaoxian; Huang, Jingyu; Zhang, Hanyu, 1964-; Du, Jiang (Actor) (Well Go USA Entertainment, 2018)
An elite Chinese assault team performs dangerous missions against Somalian pirates and rebels and terrorists in Arabian Peninsular.